Cultural and Linguistic Insights through Green Day's Lyrics for EFL Students - Arnelli, Arnelli (IKIP PGRI Pontianak, 2024)
This study explores the potential of Green Day's lyrics as an educational resource for English as a Foreign Language (EFL) learners. While traditional language instruction often lacks the cultural and emotional dimensions of authentic language, song lyrics can bridge this gap. Focusing on three Green Day songs—